Predictors of leisure activities participation and household chores in children and adolescents with Intellectual disability and autism spectrum disorder: families' perspectives - Marcos Fernando Larizzatti; Rayra Santos de Souza; Patrícia Moraes Cabral; Luiz Renato Rodrigues Carreiro; Maria Cristina Triguero Veloz Teixeira (Universidade Federal de Santa Maria (UFSM), 2024)
Carrying out domestic tasks and leisure activities in populations with atypical development has been associated with several benefits, including improvement in indicators of adaptive functioning, however, the practice of these activities by people with some disability presents low adherence. The aim of the study was to identify predictors of participation in leisure activities and household chores in children and adolescents with intellectual disability (ID) and autism spectrum disorder (ASD) (clinical group, n=62) compared to a control group of children and adolescents with typical neurodevelopment (n=62) according to parents. Parents/caregivers responded to the leisure questionnaire, Children Helping Out - Responsibilities, Expectations and Supports, Adult Self Report for Ages 18-59, Brief Problem Monitor - Parent Form for Ages 6-18, WHOQOL brief and family socioeconomic classification form. The frequency of participation (p=0.001) and leisure hours (p=0.001) were statistically lower in the clinical group compared to the control group. Children and adolescents in the clinical group had significantly more emotional and behavioral problems than the control group (attention: p=0.001; internalization: p=0.025; externalization: p=0.025), just as their parents had lower quality of life indicators (physical: p=0.003; psychological: p=0.001; social: p=0.008). The quality of personal relationships, social support and parents' sexuality were associated with the number of domestic tasks performed by their children (p=0.054). These results highlight the need for parents and caregivers of children and adolescents with ID and ASD to be involved in interventions that promote their mental health and social support, as these are fundamental to promoting the autonomy and adaptive functioning of their children.